Personal remittances in Belarus: trends and challenges - Bandarenka, Natallia (Management and Administration Journal, 2019)
In recent years, international labour migration has become an integral part of the modernworld economy. Labour migration is an important source of financial inflow for certain countries.The migrants' personal remittances sent to the country enable families to increase their consumptionlevel and a cumulative demand as well as stimulate production development. In other words,they are a tool by means of which the country can solve a complex of internal social and economicproblems more successfully. Some part of the money received is invested in development of thenational economy through purchasing shares, land and real estate. In this regard the account andcost assessment of the migrants' personal remittances are urgent. The chapter concerns the trendsof the global international migration as well as international migration in Belarus. Special attentionwill be given to detailed analysis of the size and structure of the migrants' personal remittances intheir basic elements, the countries of departure and countries of destination. The analysis is basedon the statistical data of the National Statistical Committee, the National Bank of Belarus, the Departmentof Economic and Social Affairs and Population Division of the United Nations.